1990
DOI: 10.1111/j.1528-1157.1990.tb05375.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrinology and Limbic Epilepsy: Relationships to Psychopathology, Seizure Variables, and Neuropsychological Function

Abstract: Correlations were sought among neuroendocrine, psychopathologic, neuropsychological, and seizure variables in 16 male patients with limbic epilepsy. Plasma prolactin and luteinizing hormone levels were directly correlated with seizure frequency. Plasma prolactin was inversely correlated with thought disorder. Post hoc findings included a strong direct correlation between total plasma testosterone levels and aggression. These relationships may help to elucidate mechanisms related to interictal symptomatology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Further relationships among the variables described in this article and neuroendocrine measures suggested to be of interest by Geschwind (1983) will be discussed in a companion paper (Leiderman et al, 1990). By attempting to elucidate the interrelationships among neurophysiologic, neuropsychological, endocrine, and psychopathologic factors in limbic epilepsy patients, the pathophysiology of this and other disorders that affect limbic function may be better understood.…”
Section: Psychopathology and Limbic Epileps Ymentioning
confidence: 93%
“…Further relationships among the variables described in this article and neuroendocrine measures suggested to be of interest by Geschwind (1983) will be discussed in a companion paper (Leiderman et al, 1990). By attempting to elucidate the interrelationships among neurophysiologic, neuropsychological, endocrine, and psychopathologic factors in limbic epilepsy patients, the pathophysiology of this and other disorders that affect limbic function may be better understood.…”
Section: Psychopathology and Limbic Epileps Ymentioning
confidence: 93%
“…Other studies found reduced gonadotrophin and testosterone plasma levels in the interictal state in male patients (Herzog et al. 1986 u ) and a direct correlation between seizure frequency and plasma prolactin and luteinizing hormone (LH) levels (Leiderman et al, 1990). Herzog et al (1990) recently reported an abnormal pulsatile secretion of LH in men with complex partial seizures.…”
Section: Functions F Received Junuury 29 1991)mentioning
confidence: 95%
“…1984). Leiderman et al (1990) found plasma prolactin levels to inversely correlate with thought disorder. while plasma testosterone levels correlated with aggressive behavior.…”
Section: Functions F Received Junuury 29 1991)mentioning
confidence: 99%
“…A number of experiments with laboratory animals have shown that exposure to androgens (or its metabolite estradiol) decreases the threshold at which the brain will seizure (Harden & MacLusky, 2004;Leiderman, Csernansky, & Moses, 1990;Mejıás-Aponte, Jiménez-Rivera, & Segarra, 2002). However, under some conditions, testosterone can also have anti-convulsant effects if its conversion to estradiol is blocked (Frye, Rhodes, Walf, & Harney, 2001).…”
Section: Seizuring Susceptibilitymentioning
confidence: 97%